Bronchodilator responsiveness as a predictor of success for bronchial thermoplasty. Issue 1 (31st July 2018) - Langton, David; Ing, Alvin; Fielding, David; Wang, Wei; Plummer, Virginia; Thien, Francis
ABSTRACT: Background and objective: A characteristic feature of asthma is hypertrophied airway smooth muscle, responsible for bronchoconstriction. This is the target of bronchial thermoplasty (BT). It is known that with increasing time and severity some patients develop remodelled airways with fixed airflow obstruction. The question arises whether these patients will still respond to BT. Methods: Forty‐nine consecutive severe asthmatic patients were prospectively evaluated at baseline and then 6 months after BT. The characteristics recorded included medication usage, exacerbation history, spirometry and the Asthma Control Questionnaire 5‐Item Version score (ACQ‐5). Seven patients were excluded as they did not demonstrate airflow obstruction at baseline (forced expiratory ratio (forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC)) < 70%). The remaining 42 patients were divided into two cohorts based on their response to bronchodilator. Eighteen patients in whom the FEV1 improved by at least 12% and 200 mL following bronchodilator were allocated to Group 1 (reversible). The remaining patients were allocated to Group 2 (fixed). The outcomes following BT in these two groups were then compared. Results: The patient age was 57.2 ± 12.4 years, the ACQ‐5 was 3.2 ± 1.0 and the FEV1 56.0 ± 16.4% predicted. At baseline, the patient cohorts were very similar, save for the response to bronchodilator, which was 28.1 ± 12.5% in Group 1 and 4.1 ± 5.3% in Group 2. Both groups responded to BT equally well, with significant improvements in ACQ‐5, salbutamol usage, exacerbation frequency and the weaning of oral corticosteroids. Conclusion: In patients with severe asthma, the presence or absence of variable airflow obstruction as measured by spirometry does not appear to influence outcomes from BT. Abstract : This study, in patients with severe asthma, compares the outcomes from bronchial thermoplasty (BT) in patients with fixed airflow obstruction, with patients with bronchodilator reversibility. The study concludes that both groups of patients benefit equally well from this therapy and that bronchodilator reversibility need not be a selection criterion for BT. See related Editorial